Thickness effect of sputtered ZnO seed layer on the electrical properties of Li-doped ZnO nanorods and application on the UV photodetector - Kung, C. Y.; Young, S. L.; Kao, M. C.; Chen, H. Z.; Lin, J. H.; Lin, H. H.; Horng, L.; Shih, Y. T. (2013 IEEE 5th International Nanoelectronics Conference (INEC), 2013)
Well-defined Zn 0.9 Li 0.1 O nanorods were hydrothermally synthesized at the low temperature of 90°C on the sputtered ZnO seed layer in different thickness, 20 nm and 50 nm. The x-ray diffraction patterns of both samples with a single diffraction peak (002) showed the same wurtzite hexagonal structure. The length and diameter of the nanorods were both increased from 1.12 μm to 1.47 μm and 95 nm to 113 nm, respectively, while increasing the sputtered ZnO seed layer thickness from 20 nm to 50 nm. The optical properties were influenced by the presence of oxygen vacancies induced by Li doping in the Zn 0.9 Li 0.1 O nanorods. Besides, p-type ZnO-based semiconductor nanorods were obtained by the doping of Li into ZnO. Finally, the UV photodetectors with (p-Zn 0.9 Li 0.1 O nanorods)/(n-Si substrate) structure were also achieved. The I-V characteristics of the UV photodetector with p-ZnO:Li nanorod/n-Si structure were also measured. The UV illumination/dark current ratio of the photodetectors with different seeded layer, 20nm and 50nm, were also measured as 201% and 364%, respectively.